PERANAN PEMERINTAH DALAM MEMBERANTAS PENYALAHGUNAAN DAN PERDAGANGAN OBAT-OBATAN TERLARANG - Nomensen Freddy Siahaan, Reine Rofiana dan (Universitas 17 Agustus 1945 Samarinda, 2021)
The existence of illegal drugs is getting worse day by day. There areso many ways that irresponsible parties use in an effort to smuggle theseillegal drugs. Even the role of this drug smuggler.Even more worrying, these illegal drugs have entered the territory ofthe nation's future generations (students). This can be seen from the newsquoted by the author regarding drug trafficking at the Faculty of CulturalSciences (FIB) of the University of North Sumatra (USU). Of course, thisincident made my heart cut and teary eyed because the youngergeneration, who was expected to be the baton for the next generation ofthe backbone of the country, was infiltrated by irresponsible parties in thecirculation of these illegal drugs. The news is as below.Parents and Educators (Teachers and Lecturers) each have a veryimportant role in the growth and development of children. This is theclosest person the child meets every day and can understand the child'spersonality.The role of the government in this case is represented by the NationalNarcotics Agency (BNN) taking an equally important role in eradicatingthe abuse and circulation of illegal drugs because BNN has a lot ofexperience in handling various drug cases.There should be a synergy among parents, educators, and thegovernment in eradicating the circulation of illegal drugs in order to savethe future of the nation's next generation.